2011
DOI: 10.1017/s0007114511001024
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and cognitive decline in middle-aged men and women: the Doetinchem Cohort Study

Abstract: To postpone cognitive decline and dementia in old age, primary prevention is required earlier in life during middle age. Dietary components may be modifiable determinants of mental performance. In the present study, habitual fruit and vegetable intake was studied in association with cognitive function and cognitive decline during middle age. In the Doetinchem Cohort Study, 2613 men and women aged 43-70 years at baseline (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) were examined for cognitive function twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 45 publications
13
118
4
2
Order By: Relevance
“…These results are supported by other cross sectional findings in the literature on walnuts and nut consumption in general. In one study on consumption of fruit and vegetable, including nuts, cognitive function was measured by various cognition tests and dietary intake of the subject was assessed through FFQ, and nut intake was categorized by quintiles of absolute amounts consumed (24). The global cognition function and cognitive function specifically on memory, speed and flexibility was measured using the World Verbal Learning Test (VLT) score to measure memory, the Stroop Colour World Test (SCWT) and the Letter Digit Substitution Test (LDST) to measure cognitive speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are supported by other cross sectional findings in the literature on walnuts and nut consumption in general. In one study on consumption of fruit and vegetable, including nuts, cognitive function was measured by various cognition tests and dietary intake of the subject was assessed through FFQ, and nut intake was categorized by quintiles of absolute amounts consumed (24). The global cognition function and cognitive function specifically on memory, speed and flexibility was measured using the World Verbal Learning Test (VLT) score to measure memory, the Stroop Colour World Test (SCWT) and the Letter Digit Substitution Test (LDST) to measure cognitive speed.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive tests showed that nuts consumers had better memory and cognition speed at the baseline. They reported the difference in cognitive function Volume 19, Number 3, 2015 between the lowest and the highest quintile of nut consumption as equivalent to 5-8 years difference in age (24). Another cross-sectional study on food intake and cognition among elders found that nut consumption was significantly associated with cognitive functioning as measured using six different cognition tests, which included Kendrick Object Learning Test (KOLT), Trail Making Test A (TMT-A), modified version of Digital Symbol Test (m-DST), short form of Block Design (m-BD), modified Mini -Mental State Examination (m-MMSE) and abridged version of Controlled Oral Word Association Test (S-Task) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Several factors are important for the onset of CI and CD, including female sex and the apolipoprotein Eε4 (apoEε4) genotype. 3,4 Changes in blood pressure (BP) are associated with both CI and CD in older people. 5,6 Hypertension might be implicated in the pathogenesis of poor cognition, 7 and recent studies suggest that hypotension could be a risk factor for CI and CD too.…”
mentioning
confidence: 99%
“…Over the last decade, a vast and growing research literature has been focusing on the potential of dietary polyphenols for aiding preservation of cognitive function during ageing while reducing risk for neurodegenerative disorders Nurk et al, 2009;Gu et al, 2010;Nooyens et al, 2011;Solfrizzi et al, 2011;Loef and Walach, 2012;Vauzour, 2012). For example, the regular dietary intake of polyphenol-rich foods and/or beverages has been associated with 50% reduction in the risk of dementia (Commenges et al, 2000), a preservation of cognitive performance with ageing (Morris et al, 2006;Letenneur et al, 2007), a delay in the onset of Alzheimer's disease (Dai et al, 2006;Pasinetti et al, 2015) and a reduction in the risk of developing Parkinson's disease (Checkoway et al, 2002;Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%